-2(n+4)-4n=

Simple and best practice solution for -2(n+4)-4n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(n+4)-4n= equation:


Simplifying
-2(n + 4) + -4n = 0

Reorder the terms:
-2(4 + n) + -4n = 0
(4 * -2 + n * -2) + -4n = 0
(-8 + -2n) + -4n = 0

Combine like terms: -2n + -4n = -6n
-8 + -6n = 0

Solving
-8 + -6n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -6n = 0 + 8

Combine like terms: -8 + 8 = 0
0 + -6n = 0 + 8
-6n = 0 + 8

Combine like terms: 0 + 8 = 8
-6n = 8

Divide each side by '-6'.
n = -1.333333333

Simplifying
n = -1.333333333

See similar equations:

| 1+2t=-3+4s | | 6x+2=78 | | -10=t-3 | | 23=-10(z-92)+73 | | -2k^5+8k^4= | | 8=2(6)-4 | | 8(x+y)+2x+3= | | 2(4z+2)-8=60 | | 3+6h=2h+14 | | X/5-8=3 | | (x-5)/10=10/3 | | 6x+10=31 | | (y+12)+(y-18)=180 | | 15.4+d=23 | | -4y-6=-3y-8 | | 8x=6(x-1) | | 565.2=1/3.22/7.6.6.h | | 8x^2+44x+60= | | 5x+4=46-2x | | 7+3=-5(3x-2) | | 7-2h=15-5h | | 45/w=5 | | 6x+100=10x-8 | | 1/4(11-8)=3/4 | | -8(2t+9)=-72 | | -8(2t+9)=-72t | | -5(f-67)+74=-1 | | 3m+4=7-3m | | 0=3x^3-12 | | -2(-2x-7)=30 | | 20/k=4 | | h(t)=-16t^2+15t+5 |

Equations solver categories